Evaluation Of The Implementation Of E-Pusdik Information System On The Quality Of Education Implementation In Pusdik Pancasila And Constitution - Bangkit Panji Anarogo (International Journal of Management, Innovation, and Education, 2023)
This study aims to evaluate the implementation of the e-Pusdik Information System and its impact on the quality of educational services at the Center for Pancasila and Constitutional Education (Pusdik Pancasila dan Konstitusi). The research employs a quantitative descriptive method using the Human–Organization–Technology Fit (HOT-Fit) model, which assesses the interrelationship between technological quality, user satisfaction, and organizational support in determining system effectiveness. Data were collected from educators, administrative staff, and system users through structured questionnaires and interviews to measure system reliability, service accessibility, and user responsiveness. Statistical analysis was conducted using descriptive and inferential techniques to evaluate correlations among variables representing system quality, information quality, service quality, and overall performance. The results indicate that the e-Pusdik system has been effectively implemented in supporting academic administration and learning management, although several aspects—such as data integration, user training, and interface efficiency—require continuous improvement. The study concludes that the success of e-Pusdik implementation depends not only on technological adequacy but also on user competence and institutional readiness to adopt digital transformation practices in education management. These findings highlight the importance of aligning technological innovation with organizational capacity to achieve sustainable quality improvement in educational institutions.